Effect of canal blocking on biodiversity of degraded peatlands: Insight from West Kalimantan - Muhammad Ali Imron; Farah Dini Rachmawati; Tungga Dewi; Dennis Albihad; Giot Marganti Ito Simanullang; Erin E. Poor (PLoS ONE, 2025)
Large-scale disturbance in peatland areas causes many wildlife species to suffer due to limited resources or habitat loss. Following the high attention to peatlands, some restoration efforts, such as canal blocking, have been undertaken to restore the hydrological condition of peatlands. Nonetheless, our understanding of peatland biodiversity post-canal blocking is still limited. Thus, we conducted a study in West Kalimantan to assess wildlife diversity in peatland rewetting areas and understand the canal blocking’s impact on peatland biodiversity. Surveys were conducted during both the wet and dry seasons using line transects and point counts, along with deploying autonomous recording units in four habitat types: less disturbed peat forest, disturbed peat forest, estate crop, and disturbed wet shrub. Shannon and Simpson diversity indices suggest that habitats with complex structures (i.e., forested habitat) support higher diversity compared to those with open and uniform vegetation (i.e., non-forested habitat). This notion is also supported by acoustic indices calculations, which indicate that forested areas show higher acoustic diversity (biophony), and thus higher biodiversity compared to non-forested areas. However, our results indicate that there is insufficient evidence to suggest the effect of canal blocking on wildlife diversity in all rewetting sites. Aligning biodiversity conservation efforts with the natural climate solutions hierarchy, which is part of nature-based solutions and consists of protect, manage, and restore, could offer promising solutions for recovering the sites.